PWE-227 Outcome of cytomegalovirus colitis in patients with IBD—experience from Royal United Hospital Bath!. (28th May 2012) - Ahmed, I; Kalsi, N; Lane, I; Biddlestone, L; Mehta, T
Abstract : Introduction: CMV infection has been described in patients with inflammatory bowel disease (IBD). It is considered to be responsible for relapse, increased severity and poor outcome if left untreated. Ganciclovir is the mainstay of treatment but data regarding its use, mode of administration and duration of treatment is poorly described. Studies have demonstrated favourable outcome with the use of antiviral treatment. Methods: We studied the medical records of patients with IBD and concurrent diagnosis of CMV since 2005. Record of investigations was obtained from hospital electronic resources. The parameters studied were duration and mode of treatment with Ganciclovir, clinical scoring using Harvey Bradshaw Index (HBI), CRP pre-treatment and on day 3, 7 and 14th of treatment, CMV PCR pre and post-treatment, detection of Clostridium difficile toxins (CDT) and outcome in term of colectomy or clinical improvement. Results: 13 patients with pre-existing diagnosis of IBD (UC=8, CD=3, non-specific colitis=2) were identified with a confirmed diagnosis of CMV on colonic biopsies between 2005 and 2011. The age range was 33–91 yrs (mean=68, F=6). 11/13 patients were admitted to hospital with flare of IBD and were steroid refractory. One was admitted with severe diarrhoea without IBD and the other had colectomy for severe UC and was found with CMV in the colectomy specimen. Out of 13, 11 patients were treated with Ganciclovir: six with 2 weeks of intravenous Ganciclovir 5 mg/kg, 3 with 1 week of intravenous and 2 with 1 week of intravenous followed by 2 weeks of oral Valganciclovir. Out of those treated, eight patients improved and were discharged, and three required colectomy. All six patients who received 2 weeks of intravenous treatment improved and were discharged. All three who required colectomy had 1 week of intravenous treatment and one had additional oral Vanganciclovir. CRP response was found to be non-predictive but improvement in HBI on day 3 of treatment was found to be associated with better outcome. None of the patients were positive for CDT. Conclusion: CMV colitis is associated with poor outcome in patient with IBD if left untreated. Data regarding mode and duration of treatment remain poorly defined; in our experience 2 weeks of intravenous Ganciclovir was associated with a better outcome. Little or no improvement in the clinical condition on day 3 of treatment was associated with colectomy. Further data are required to evaluate the treatment guidance of this condition. Competing interests: None declared. References: 1. European Evidence-Based Consensus on the Prevention, Diagnosis and Management of Opportunistic Infections in iBD, ECCO Guidelines . 2009. 2. Garrett Lawlor MD, Alan C, Moss MD. CMV in IBD: Pathogen or innocent bystander? Inflamm Bowel Dis 2010;16 :1620–7.